PARADIGMA DAKWAH ISLAM TERHADAP BUDAYA LOKAL NYADRAN DI DESA GENDINGAN, WIDODAREN, NGAWI - Husna, Atifa Zahra Asmaul (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
This article examines the Islamic da'wah paradigm towards Nyadran local culture in Gendingan Village, Widodaren, Ngawi, using Pierre Bourdieu's habitus theory as an analytical framework. This research uses descriptive qualitative method, involving observation, interview, and literature study. The results showed that Nyadran tradition is a manifestation of integration between Islamic values and local culture, reflecting a harmonious acculturation process. Bourdieu's habitus theory helps understand how Nyadran becomes an integral part of the identity and behavior of the local community. Islamic Da'wah in the area needs to consider local habitus to be well received, respecting local cultural values while maintaining the essence of Islamic teachings. The Nyadran tradition not only functions as a religious ritual, but also as an instrument to strengthen social cohesion and collective identity of the community. An inclusive and contextual da'wah approach has the potential to enrich the meaning of local traditions, making it a medium to bring people closer to Islamic values without losing their cultural identity.